ANALYSIS OF THE INFLUENCE OF INCENTIVES AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE OF GUNAWANGSA GROUP SURABAYA - Utomo, Priyo; Arifin, Syamsul; Setyowati, Indah (2021)
This research aims to identify the effect of incentives and work motivation on the performance of employees of Gunawangsa Group Surabaya. This research method used quantitative descriptive. The population in this research is all employees of Gunawangsa Group Surabaya. The illustration of this research is 65 people. Taking illustrations using the saturated sampling method (total sampling). Information was collected using a questionnaire form. The analysis of information in this research uses multiple linear regression analysis methods and is processed using the SPSS 16 application. The results of this research show that incentives do not affect the employee performance of Gunawangsa Group Surabaya, indicated by the t value is smaller than the t table value (0.138 <1.990 ). Work motivation has a significant influence on the employee performance of Gunawangsa Group Surabaya, this is indicated by the t value is greater than the t table (2,960> 1,990). Incentives and work motivation simultaneously have a significant effect on the performance of Gunawangsa Group Surabaya employees, indicated by the calculated F value are greater than the F table value (6,017> 3.07) with a significance level of 5%.